Wealth, cost, and misperception: Empirical estimation of three interaction channels in a financial-macroeconomic agent-based model - Jiri Kukacka; Erik Zila (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Financial-macroeconomic agent-based models offer a promising avenue for understanding complex economic interactions, but their use is hindered by challenging empirical estimation. Our paper addresses this gap by constructing a stylized integrated model and estimating its core parameters using US data from 1954 to 2022. To tackle econometric obstacles, including mixed data frequencies, we adapt the simulated method of moments. We then focus on three key interaction channels. The stock market influences the real sector through the wealth effect, which boosts current consumption, and the cost effect, which lowers financing costs for firms. Conversely, the real economy impacts the stock market via the price misperception effect, where economic conditions help approximate the fundamental value of stocks. Our results provide strong statistical support for all three channels, offering novel empirical insights into critical dynamics between the two sectors of the economy.
Keywords: C13; C53; E12; G41; E71; 330; integrated agent-based model; behavioral finance and macroeconomics; bounded rationality; heuristic switching; simulated method of moments